2020
DOI: 10.1093/jas/skaa278.209
|View full text |Cite
|
Sign up to set email alerts
|

150 Effects of managing mature beef bulls on divergent planes of nutrition on novel measures of bull fertility

Abstract: Fifteen mature beef bulls (BW = 800.4 ± 17.4 kg) were used in a 112-d experiment to evaluate effects of divergent planes of nutrition on novel measures of bull fertility. Bulls were ranked by BW and randomly assigned to one of two treatments: 1) managed on a positive plane of nutrition (POS, n = 8), or 2) managed on a negative plane of nutrition (NEG, n = 7). Bulls were individually fed a common diet adjusted biweekly to achieve targeted weight loss or gain of 12.5% of original BW. On d 112, electroejaculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Only minor changes occurred in the seminal microbial composition in response to differential gains. Previous studies indicated that a negative plane of nutrition during spermatogenesis can have an impact on sperm motility and kinematic properties in mature beef bulls [41]. Our results suggest that the microbial community associated with bovine semen is resilient to plane of nutrition, and this might be due to the fact that the same dietary composition was included in the diet fed to both MOD and HIGH bulls.…”
Section: Discussionmentioning
confidence: 54%
“…Only minor changes occurred in the seminal microbial composition in response to differential gains. Previous studies indicated that a negative plane of nutrition during spermatogenesis can have an impact on sperm motility and kinematic properties in mature beef bulls [41]. Our results suggest that the microbial community associated with bovine semen is resilient to plane of nutrition, and this might be due to the fact that the same dietary composition was included in the diet fed to both MOD and HIGH bulls.…”
Section: Discussionmentioning
confidence: 54%
“…Only minor changes occurred in the seminal microbial composition in response to differential gains. Previous studies indicated that a negative plane of nutrition during spermatogenesis can have an impact on sperm motility and kinematic properties in mature beef bulls ( 31 ). Our results suggest that the microbial community associated with bovine semen is resilient to the plane of nutrition, and this might be due to the inclusion of the same dietary composition in the diet fed to both moderate and high bulls.…”
Section: Discussionmentioning
confidence: 99%